Evaluating the potentiality of Shivalik Fossil Park as emerging Indian national geopark - Vidhi Saluja; Subhash Anand; Rabindra Nath Dubey (National Geographical Journal of India, 2022)
The paper aims to present the Shivalik fossil park as a potential geopark and geotourism destination. The paper also briefly discusses and analyses the existing problems and essential criteria’s that are preventing the area from becoming a geopark at the moment. The region of Sirmaur district where the park is located has the highest concentration of fossils in Himachal Pradesh. This makes Shivalik fossil park a good candidate for becoming a geopark in the future. Despite its rich geodiversity, this region lacks the infrastructure and qualified staff required for further development of the area. The main purpose of the aper is to evaluate the major factors responsible for the development of geopark at Shivaliks fossil park. The aims and objectives of the paper are achieved through the use of mixed methods (Qualitative and Quantitative) which help in attaining holistic viewpoints of the persons involved, as well as to measure the perception of the local communities with the help of a primary survey. The correlation method, community participation model and matrix analysis was performed to highlight the role of local communities in the promotion and development of geopark in their respective area. The ndings of the study show that Shivalik fossil park fully meets only the basic criterion necessary for the declaration of a geopark.